Enhanced oxidative stress and platelet activation in patients with Cushing's syndrome. (2nd July 2014) - Karamouzis, Ioannis; Berardelli, Rita; D'Angelo, Valentina; Fussotto, Beatrice; Zichi, Clizia; Giordano, Roberta; Settanni, Fabio; Maccario, Mauro; Ghigo, Ezio; Arvat, Emanuela
Summary Objective Cushing Syndrome (CS) is implicated by increased cardiovascular risk (CVR) leading to increased morbidity and mortality. Oxidative stress (OS) and platelet activation (PA) are associated with increased CVR. However, scarce data of OS in CS exist. Our objective was to determine the oxidant–antioxidant balance in CS. Design Fourteen patients with CS at diagnosis and fourteen healthy subjects (NS) were evaluated OS by measuring plasma 15‐F2t‐Isoprostane (15‐F2t‐IsoP), PA by thromboxaneB2 levels (TXB2), and antioxidant reserve measuring total antioxidant capacity (TAC) and serum vitamin E. Results 15‐F2t‐IsoP and TXB2 levels were significantly higher (P < 0·01) in CS, while vitamin E levels were higher in NS (P < 0·03). 15‐F2t‐IsoP levels were significantly higher (P < 0·01) in complicated vs not‐complicated CS and NS and significantly higher (P < 0·03) in CS not‐complicated vs NS. TXB2 levels were significantly reduced (P < 0·03) in NS vs complicated and not‐complicated CS. A negative correlation between Vitamin E and UFC was observed in CS (P < 0·05 r = −0·497). TXB2 correlated with glucose, HbA1c and T‐score (P < 0·05 r = 0·512, P < 0·03 r = 0·527 and P < 0·01 r = 0·783, respectively) and HDL (P < 0·01 r = −0·651). 15‐F2t‐IsoP correlated with triglicerides, HbA1c and diastolic pressure (P < 0·01 r = 0·650, P < 0·03 r = 0·571 and P < 0·05 r = 0·498, respectively) and HDL (P < 0·03 r = −0·594). Conclusions This study emphasizes the major role of OS in CS. As our findings demonstrated that enhanced OS and PA take place in this rare metabolic disorder which is associated with increased CVR, it could be suggested that these biochemical alterations can further contribute in the pathogenesis of atherosclerosis, increased CVR and mortality in CS.